Effect of lamina fiber orientation interfaced with semi-flexible adhesive layer on strength and failure mode of composite single-lap joints. (October 2022) - Sadeghi, Ali; Mahshid, Rasoul; Heidari-Rarani, Mohammad; Lessard, Larry
Abstract: Various geometric and material parameters such as adhesive thickness, adhesive overlap, adherend thickness, and composite layup may affect the strength of the joint under quasi-static loading and failure mode of bonded composite-to-composite single-lap joints (SLJs) and are investigated by previous studies. The study herein broadens these findings by looking into the effect of lamina fiber angle adjacent to the adhesive layer on the damage initiation and evolution in detail. In this regard, a composite-to-composite adhesively bonded SLJ with adherends made of E-glass/epoxy composites and [04 // θ /03 ] (where//shows the adhesive location) layups are manufactured and tested under quasi-static tensile loading. The adhesive type is semi-flexible Araldite 2015. Experimental results show that by increasing the fiber angle from 0 ° to 90 °, the shear stress in the adhesive layer is decreased while the peel stress is increased. In examining typical fracture interfaces for each layup configuration, a full description of failure mode assessment is obtained. In particular, the SLJ is modeled in Abaqus using cohesive elements with bilinear traction-separation law. Numerical results indicate that the bilinear cohesive law cannot model the exact load-displacement curve due to semi-flexible behavior of the epoxy adhesive, but it can predict maximum strength precisely. The failure of composite joints is significantly influenced by shear stress.